DFSMShsm fast replication technical guide - Winnard, Keith; Vangsness, Jeanne (IBM Corporation, International Technical Support Organization, 2015)
DFSMShsm fast replication provides DFSMShsm management for the use of volume-level fast replication. Fast replication is made possible by using the FlashCopy® capability of storage servers. With this capability, a set of storage groups can be defined as a copy pool. The volumes in this pool are processed collectively creating, by fast replication, backup versions that are managed by DFSMShsm. Recovery can be performed at the volume or copy pool level. This capability is designed to work specifically with DB2® Version 8 or later. With DFSMShsm fast replication, the backup and recovery of DB2 copy pools can be managed by DFSMShsm. DFSMShsm fast replication provides a quick, easy-to-use backup and recovery solution. This IBM® Redbooks® publication consists of a technical overview of the DFSMShsm fast replication function in z/OS® V1R12 Data Facility Storage Management Subsystem (DFSMS). It provides you with the information that you need to understand and evaluate the function, with practical implementation hints and tips. This book is written for storage professionals, database administrators, and system programmers who have experience with the components of DFSMS. It provides sufficient information for you to implement the DFSMShsm fast replication function in your storage environment.
"Z systems"--Cover. - Number on resource description page: SG24706902. - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed May 20, 2015)
Keywords: Electronic data processing -- Backup processing alternatives; Data recovery (Computer science); Sauvegarde (Informatique); Récupération des données (Informatique); Electronic data processing; Backup processing alternatives